Building Relations: The Creation of Eau Claire’s Town Gown Community - Shrader, Erica (My University, 2017)
The University of Wisconsin-Eau Claire has had a large impact on the city it resides in. Through enlargement of the campus and increased student population, the University has been able to change the make-up of the downtown area. This can especially be seen through examining the changes the popular Water Street has gone through since the University was built. This essay will explore the increase in the student population and the growth of the University’s campus and how that has directly affected the makeup of Water Street. Looking at the years 1920-1930, 1960-1970, and 1990-2000 it can be seen how Water Street has been reshaped to serve primarily the needs of the University of Wisconsin-Eau Claire and its students, faculty, and staff. This will be done by exploring changes in businesses, interactions between the community and the University, and residential patterns in the nearby area of Water Street. The analysis of documents by the city manager, historical data from the Eau Claire City Directories, and census data of the Water Street district provide the information to understand these changes. This paper contributes to the overall understanding of the impact that the University has had on the Eau Claire area in a non-academic way. Types of businesses that have come and gone and how houses and their residents have changed all impact Eau Claire overall, and they are the result of the University.
Keywords: University of Wisconsin-Eau Claire--History; Universities and colleges--Wisconsin--Eau Claire; University of Wisconsin--Eau Claire--Student life; Eau Claire (Wis.); City planning--Wisconsin--Eau Claire; Water Street (Eau Claire, Wis.)